Molecular Genetics and Epidemiology of Vitiligo: A Minireview - Shahrzad Aghaeii; Masoud Amiri; Maryam Aghaei; Mohammad Ali Nilforoushzadeh (Shahrekord University of Medical Sciences, 2018)
Background and aims: Vitiligo is an acquired, idiopathic, and common depigmentation disorder of the skin that affects people of all ages and both sexes equally worldwide. Although etiology of the disease is unknown, there are theories such as environment and genetic factors. Methods: In this article, we collected and summarized the appropriate manuscripts regarding the epidemiology and genetics using the terms vitiligo and genetic epidemiology in PubMed and Google Scholar. Results: Studies showed the highest prevalence of disease in African countries, but with regard to the distribution of disease in different areas, environmental factors were as important as other causes of vitiligo, and 3 genes of FOXP3, XBP1 and TSLP had the most association with the disease. Conclusion: It seems that recognition of the genetic basis of vitiligo will supply new insight into the therapies for it. Therefore, more genetic studies are needed to discover the genes and causes linked to clinical aspects of this disease.